2020
DOI: 10.1016/j.scitotenv.2020.138812
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with negative conversion of viral RNA in patients hospitalized with COVID-19

Abstract: Journal Pre-proof J o u r n a l P r e -p r o o f Journal Pre-proof J o u r n a l P r e -p r o o f 3 Abstract Factors associated with negative conversion of SARS-CoV-2 RNA in hospitalized patients have not yet been systematically determined. We conducted a retrospective cohort study of COVID-19 patients in Qingdao, China. Both univariate and multivariate analysis were performed to identify independent factors for time to viral RNA negative conversion. Data on patients with re-detectable viral RNA after showing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
149
8
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(186 citation statements)
references
References 22 publications
27
149
8
2
Order By: Relevance
“…Interestingly, Hu et al. found than headache was associated with intermittent negative SARS-CoV-2 RT-PCR status (16), highlighting our results about headache in the multivariate analysis.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Interestingly, Hu et al. found than headache was associated with intermittent negative SARS-CoV-2 RT-PCR status (16), highlighting our results about headache in the multivariate analysis.…”
Section: Discussionsupporting
confidence: 68%
“…The proportion of "case" and "control" patients who received at least one treatment (chloroquine, corticosteroids, lopinavir/ritonavir, macrolids or tocilizumab) did not differ (P=0.26) ( Table 3). Mechanical ventilation was required for 10 (12.7%) cases and 14 (17.7%) controls (P=0.177), for a duration of 21 [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] days for cases and 15 [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] days for controls (P=0.197).…”
Section: Betweenmentioning
confidence: 99%
“…Hu et al determined the time to negative conversion of viral RNA in patients hospitalized with Covid-19 infection [15]. The median time from the first day of a positive RNA test to consecutive negative tests was 14 (IQR 10-18) days.…”
Section: Viremia and Viral Loadmentioning
confidence: 99%
“…For every 1 unit increase in Ct, the odds ratio for infectivity decreases by 32%. Some studies also reported that viral infectivity in patients with symptoms' duration > 8 days may be low [16,17]. Several factors might affect the occurrence of prolonged nucleic acid conversion, including older age, having comorbidities, such as diabetes and hypertension, and impaired immune function [18].…”
Section: Discussionmentioning
confidence: 99%